2004
DOI: 10.1159/000077804
|View full text |Cite
|
Sign up to set email alerts
|

Differential Efficacy of Clarithromycin in Lung versus Thigh Infection Models

Abstract: Background: Differences in clarithromycin disposition and the resulting changes in bacterial density were studied using mouse lung and thigh infection models. Methods: Clarithromycin activity was evaluated against seven Streptococcus pneumoniae isolates with efflux-mediated resistance in both murine lung and thigh infection models. Intrapulmonary disposition of clarithromycin was also studied. Results: Consistent bacterial kill was observed in the lung model, whereas no drug effect was observed in the thigh mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…In contrast, the mean R. equi CFU in the lungs were lower in mice receiving CLR monotherapy than in saline controls. The preferential activity of CLR in the lungs has been documented previously, presumably because of the high concentrations achieved in the pulmonary epithelial lining fluid (22).…”
supporting
confidence: 55%
“…In contrast, the mean R. equi CFU in the lungs were lower in mice receiving CLR monotherapy than in saline controls. The preferential activity of CLR in the lungs has been documented previously, presumably because of the high concentrations achieved in the pulmonary epithelial lining fluid (22).…”
supporting
confidence: 55%
“…Agents Chemother., abstr. A-1097, 2001) conducted with clarithromycin and three S. pneumoniae strains, the doses of the antimicrobial used in that study (0.38 to 48 mg/kg administered every 6 h) were considerably different from the regimen of 200 mg/kg administered every 12 h used in our previous study (12). As a result of these murine studies, we must interpret the data that have been generated with the thigh infection model cautiously when assessing the magnitude of exposure required to ensure microbiologic eradication by treatment with telithromycin in humans, since this compound also displays the ability to accumulate in epithelial lining fluid, as the concentrations at this pulmonary site exceed the corresponding concentrations in plasma (10,13).…”
Section: Discussionmentioning
confidence: 74%
“…As a result, while the pharmacodynamic parameter most predictive of outcome (i.e., AUC/MIC) remains constant in the absence or the presence of neutrophils, the magnitude of drug exposure required to produce any given reduction in bacterial density is substantially reduced in the immunocompetent host. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]1998) evaluated the impacts of neutrophils on the bacteriostatic activity of telithromycin and a structurally related ketolide against S. pneumoniae strains with various macrolide susceptibilities in the murine thigh infection model and reported that the potencies of the ketolides are enhanced (1.8-to 24-fold) in the presence of neutrophils. Moreover, although neutropenic conditions were used in the present study, the enhanced in vivo potency of another ketolide, ABT-773, against pneumococci in immunocompetent hosts has also recently been demonstrated (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor playing a significant role is drug concentration at the site of infection. Antimicrobials such as macrolides and telithromycin have been shown to be sequestered in macrophages and in the epithelial lining fluid of the lungs [6][7][8].…”
Section: Discussionmentioning
confidence: 99%